Contemplative pedagogy: a descriptive account of two approaches to student engagement at Loyola Marymount University - Brucker, Jane (International journal of Dharma Studies, 2017)
In this article the alternating voices of colleagues and collaborators Jane Brucker and Christopher Chapple describe their way of using contemplative pedagogies to bring Engaged Learning to their students at Loyola Marymount University. A requirement of the curriculum for all undergraduate students, these courses integrate study and reflection beyond the classroom. As a professor of studio arts, Brucker has developed techniques of awareness that utilize a contemplative approach with students engaged in drawing and creative activity in a studio or off-campus setting. As a professor of comparative theology, Chapple has designed course requirements for meditation experience and field visits that embed his students within the contemplative aspects of Buddhism as well as in communities deeply grounded in environmental action. Grounded in the Jesuit-Marymount concern for educating the whole person', Brucker and Chapple understand this as engaging students in experiences that include the relationship between the inner experience of meditation and the outward experiences of spirituality, creativity, and nature.